PENGARUH LATIHAN PASSING BAWAH BERPASANGAN DAN DRILL INDIVIDU TERHADAP KEMAMPUAN PASSING BAWAH BOLA VOLI - JAYANTI, KARTIKA DWI (Universitas Negeri Semarang, 2021)
The main problems is often to make mistakes in the underpass technique. The purpose of the study was to find out whether there was an effect of pair bottom passing practice, individual drill and which one had more influence on the volleyball bottom passing ability of the women's volleyball extracurricular participants at SMP Negeri 3 Ungaran. This study uses an experimental method with the form of research design